Investigation of the impact of cognitive load on EFL learners’ satisfaction with MOOCs: the mediating role of expectation confirmation and perceived usefulness - Lingling Ma (BMC Psychology)
Abstract MOOCs as a flexible form of online education, have gained increasing popularity among EFL learners. However, the impact of cognitive load on learners’ satisfaction has not been thoroughly explored. This study, grounded in Cognitive Load Theory and Expectation Confirmation Theory, empirically investigates the effects of cognitive load, confirmation, and perceived usefulness on EFL learners’ satisfaction with MOOCs. This study collected 293 valid questionnaire responses through an online survey, with data collection occurring from March 2024 to August 2024. The data were analyzed using Structural Equation Modeling (PLS-SEM). The results show that cognitive load significantly negatively affects EFL learners’ confirmation (β = -0.391, p < 0.001), perceived usefulness (β = -0.808, p < 0.001), and satisfaction (β = -0.187, p < 0.001) with MOOCs. Confirmation positively influences learners’ perceived usefulness (β = 0.763, p < 0.001) and satisfaction (β = 0.231, p < 0.001), perceived usefulness significantly positively influences learners’ satisfaction (β = 0.571, p < 0.001). Additionally, confirmation (β = -0.090, p < 0.001) and perceived usefulness (β = -0.461, p < 0.001) partially mediate the relationship between cognitive load and satisfaction. The findings provide practical implications for MOOC platform designers in optimizing course content and reducing cognitive load to enhance learner satisfaction. Finally, the theoretical and practical significance of the study’s results is discussed.